Direct Determination of Flavanone Isomers in Citrus Juice by Paper Spray Tandem Mass Spectrometry - Lucia Bartella; Fabio Mazzotti; Ilaria Santoro; Ines Rosita Talarico; Leonardo Di Donna (Antioxidants)
A novel and efficient analytical protocol based on paper spray tandem mass spectrometry was developed for the determination of isomeric O-glycoside flavanones in citrus juices and beverages. This approach significantly reduces sample preparation time and solvent consumption compared to traditional chromatographic techniques. By exploiting the unique fragmentation patterns of these compounds, accurate quantification of both diglycosides and their individual isomers (neohesperidoside and rutinose derivatives) was achieved. The method demonstrated excellent analytical performance, with high accuracy, selectivity, and reproducibility. The impact of matrix effects was mitigated through the construction of ratio calibration curves, ensuring reliable quantification in complex matrices. Finally, a simple DPPH experiment to assay the antioxidant activity of each single positional isomer was performed, indicating the superior ability of neohesperidose conjugates. This simplified method offers a valuable tool for quality control, authenticity assessment and the study of health benefits associated with citrus consumption.